Impacts of 3 years of elevated atmospheric CO2 on rhizosphere carbon flow and microbial community dynamics. (7th November 2012) - Drigo, Barbara; Kowalchuk, George A.; Knapp, Brigitte A.; Pijl, Agata S.; Boschker, Henricus T. S.; van, Johannes A.
Abstract Carbon (C) uptake by terrestrial ecosystems represents an important option for partially mitigating anthropogenic CO2 emissions. Short‐term atmospheric elevated CO2 exposure has been shown to create major shifts in C flow routes and diversity of the active soil‐borne microbial community. Long‐term increases in CO2 have been hypothesized to have subtle effects due to the potential adaptation of soil microorganism to the increased flow of organic C. Here, we studied the effects of prolonged elevated atmospheric CO2 exposure on microbial C flow and microbial communities in the rhizosphere. Carex arenaria (a nonmycorrhizal plant species) and Festuca rubra (a mycorrhizal plant species) were grown at defined atmospheric conditions differing in CO2 concentration (350 and 700 ppm) for 3 years. During this period, C flow was assessed repeatedly (after 6 months, 1, 2, and 3 years) by 13C pulse‐chase experiments, and label was tracked through the rhizosphere bacterial, general fungal, and arbuscular mycorrhizal fungal (AMF) communities. Fatty acid biomarker analyses and RNA‐stable isotope probing (RNA‐SIP), in combination with real‐time PCR and PCR‐DGGE, were used to examine microbial community dynamics and abundance. Throughout the experiment the influence of elevated CO2 was highly plant dependent, with the mycorrhizal plant exerting a greater influence on both bacterial and fungal communities. Biomarker data confirmed that rhizodeposited C was first processed by AMF and subsequently transferred to bacterial and fungal communities in the rhizosphere soil. Over the course of 3 years, elevated CO2 caused a continuous increase in the 13C enrichment retained in AMF and an increasing delay in the transfer of C to the bacterial community. These results show that, not only do elevated atmospheric CO2 conditions induce changes in rhizosphere C flow and dynamics but also continue to develop over multiple seasons, thereby affecting terrestrial ecosystems C utilization processes.